Evaluating The Impact Of Chess Learning On Children With Autism Spectrum Disorders - Sargsyan, Vahan; Sargsyan, Tamara; Nersisyan, Sona; Gevorgyan, Nune
Chess Scientific Research Institute examined the impact of learning chess on children with Autism Spectrum Disorders (ASD). Using a mixed-methods approach that combined qualitative data collecting and quantitative analysis, it sought to determine how chess affects these kids' cognitive, social, and behavioral development. The results showed that although children with more developed verbal skills had more excellent chess development, behavioral features, and other factors also had a significant impact on their learning outcomes. Eye contact and engagement levels varied even when communication and social interactions improved. The study emphasizes the need for more research and individualized teaching strategies to prove that chess is a valuable tool for helping kids with ASD.
Keywords: Education